Reader's Response To Domestic Violence In Nicholas Sparks's Safe Haven Novel (2010) - A'isa, Nurul; , Dr. M. Thoyibi, MS (2017)
This study aims to investigate reader's response to domestic violence in Safe Haven novel (2010) by Nicholas Sparks. This research belongs to qualitative. In analyzing reader's response, the researcher uses Richard Beach theory of reader's response. The primary data source is reader's response of Safe Haven novel taken from goodreads website. The secondary data sources are other sources such as journals and articles related to the primary data. The result of this research shows following conclusion. First, there are five dominant issues reviewed by the reader in Safe Haven novel, namely character and characterization, ending of the story, domestic violence, message of the story, and adaptation to movie. Second, the background of the reviewers belongs to male and female gender that comes from America, Asia, Europe, Australia, and Africa. Those responses come from 2010 until 2017. Third, domestic violence issue divided into two topics such as the cause of domestic violence and the effect of domestic violence. Domestic violence caused by abusive relationship, psychopath , danger, and horror, while the effect domestic violence are traumatic and run away wife.